Comparison of lyophilized versus liquid modified vaccinia Ankara (MVA) formulations and subcutaneous versus intradermal routes of administration in healthy vaccinia-naïve subjects - Frey, Sharon E.; Wald, Anna; Edupuganti, Srilatha; Jackson, Lisa A.; Stapleton, Jack T.; Sahly, Hana El; El-Kamary, Samer S.; Edwards, Kathryn; Keyserling, Harry; Winokur, Patricia; Keitel, Wendy; Hill, Heather; et al. (Vaccine, 2015)
•Lyophilized MVA was more immunogenic than the current liquid formulation of MVA.•The lower ID dose of MVA was immunologically non-inferior to the standard SC dose.•The ID route resulted in more erythema and/or induration than the SC route.•The ID route may increase the number of available doses in an emergency situation. Modified vaccinia Ankara (MVA) is being developed as a safer smallpox vaccine and is being placed in the US Strategic National Stockpile (SNS) as a liquid formulation for subcutaneous (SC) administration at a dose of 1×108 TCID50 in a volume of 0.5mL. This study compared the safety and immunogenicity of the standard formulation, dose and route with both a more stable, lyophilized formulation and with an antigen-sparing intradermal (ID) route of administration. 524 subjects were randomized to receive either a full dose of Lyophilized-SC, a full dose of Liquid-SC or 20% (2×107 TCID50 in 0.1mL) of a full dose Liquid-ID MVA on Days 0 and 28. Safety and immunogenicity were followed through 180 days post second vaccination. Among the 3 groups, the proportion of subjects with moderate/severe functional local reactions was significantly different (P=0.0013) between the Lyophilized-SC group (30.3%), the Liquid-SC group (13.8%) and Liquid-ID group (22.0%) only after first vaccination; and for moderate/severe measured erythema and/or induration after any vaccination (P=0.0001) between the Lyophilized-SC group (58.2%), the Liquid-SC group (58.1%) and the Liquid-ID group (94.8%) and the reactions lasted longer in the Liquid-ID group. In the ID Group, 36.1% of subjects had mild injection site skin discoloration lasting ≥6 months. After second vaccination Day (42–208), geometric mean of peak neutralization titers were 87.8, 49.5 and 59.5 for the Lyophilized-SC, Liquid-SC and Liquid-ID groups, respectively, and the maximum number of responders based on peak titer in each group was 142/145 (97.9%), 142/149 (95.3%) and 138/146 (94.5%), respectively. At 180 days after the second vaccination, geometric mean neutralization titers declined to 11.7, 10.2 and 10.4 with only 54.3%, 39.2% and 35.2% of subjects remaining seropositive for the Lyophilized-SC, Liquid-SC and Liquid-ID groups, respectively. Both the Lyophilized-SC and Liquid-ID groups were considered non-inferior (primary objective) to the Liquid-SC group. Transitioning to a lyophilized formulation, which has a longer shelf life, will not negatively impact immunogenicity. In a situation where insufficient vaccine is available, ID vaccination could be used, increasing the number of available doses of vaccine in the SNS 5-fold (i.e., from 20 million to 100 million doses).